Laparoscopy & robotics: a historical parallel - MIGUEL PRESTES NACUL (Revista do Colégio Brasileiro de Cirurgiões, 2020)
ABSTRACT The evolution of robotic platforms has brought up ethical, economic, educational, and clinical applicability issues that refer to the early 1990s, when laparoscopy began its dissemination as a technology that would revolutionize surgery. Introduced in Brazil since 1990, laparoscopy has received a lot of resistance from different sectors, including the medical academy itself. The technique was considered expensive, complex, poorly available and with limited clinical applications. However, in a short time, it was established as the gold standard for the treatment of most diseases in different organ systems and surgical specialties. At this time, similarly to laparoscopy, robotic surgery is expressed as a disruptive technology, determining an important breakdown of paradigms, and moving the wheel of history forward. The author draws a parallel in relation to the use of both technologies in the surgeon’s armamentarium. The fear of the “new technology”, seen when laparoscopy appeared, is repeated with the advent of robotic surgery. Laparoscopy and robotic surgery, at the same time, imposed new knowledge challenges for surgeons, anesthetists, nurses, engineers - the need to learn again, to develop new skills. The previous experience of implementing laparoscopy should always be remembered and considered, optimizing the current scenario of the robotic platform, in its introduction and dissemination with the surgical community. The advent of the “robotic era” and its evolutionary potential will continue to assist surgeons in their mission to serve their patients with quality and safety.